2015
DOI: 10.1002/anie.201508107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Supported Ultrafine Non‐noble Subnanometer‐Scale Metal Particles Derived from Metal–Organic Frameworks as Highly Efficient Heterogeneous Catalysts

Abstract: The properties of supported non-noble metal particles with a size of less than 1 nm are unknown because their synthesis is a challenge. A strategy has now been created to immobilize ultrafine non-noble metal particles on supports using metal-organic frameworks (MOFs) as metal precursors. Ni/SiO2 and Co/SiO2 catalysts were synthesized with an average metal particle size of 0.9 nm. The metal nanoparticles were immobilized uniformly on the support with a metal loading of about 20 wt%. Interestingly, the ultrafine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…The high‐resolution TEM image presented in Figure d shows Ni NPs of approximately 5 nm, and the (1 1 1) plane can be identified easily according to the lattice fringe of 0.202 nm. Notably, the preparation of nano‐sized Ni catalysts, especially with particle size less than 10 nm and with a very high loading, remains a great challenge …”
Section: Resultsmentioning
confidence: 98%
“…The high‐resolution TEM image presented in Figure d shows Ni NPs of approximately 5 nm, and the (1 1 1) plane can be identified easily according to the lattice fringe of 0.202 nm. Notably, the preparation of nano‐sized Ni catalysts, especially with particle size less than 10 nm and with a very high loading, remains a great challenge …”
Section: Resultsmentioning
confidence: 98%
“…[23][24][25][26] Taking advantage of this category of the systems, we demonstrate a facile synthetic route to fabricate hollow hierarchical Ni@C nanocomposite by one-step solid-state pyrolysis of a simple and inexpensive organic-inorganic layered nickel hydroxides. In this facile procedure, cheap commercially available nickel nitrate hexahydrate and sodium salicylate are used as starting materials, and during the pyrolysis process the interlayer salicylate anions act as carbon source and reducing agent without the need for any external agent or surface modication.…”
Section: -7mentioning
confidence: 99%
“…[4] This is driven by the fact that the metal building blocks are well defined and, more often than not, highly dispersed. [7] While numerousw orks show exceptional catalytic properties of MOF-derived carbons containing metal or metal oxide NPs, the use of MOF-derived transition-metal sulfides,p hosphides, and carbides for thermally driven organic transformations only recently made its debut. [5] Compared with traditional methods for the impregnationo fp orous supports with NPs, the dispersity andh omogeneity of which is often not well controlled, MOF-derived materials promote the creation of small, homogeneous, catalytically active species inside the resulting mesoporous carbon networks.F or example, Li et al recently reported highly dispersed single cobalt atoms and Fe-Co dual sites embedded in N-doped porous carbon.T his material, createdt hrough the pyrolysis of ap redesignedb imetallic Zn/Co MOF, [6] was shown to be highly efficient in the electrochemical oxygen reduction reaction.…”
Section: Introductionmentioning
confidence: 99%